(untitled) (International Journal of Engineering and Computer Science, 2014)
Several information channels are required with several different RF transmission frequencies for wireless communication because of requirements of many selective RF receivers. This requirement leads to the complex network which indirectly increases the cost of the system. This paper provides the solution for the above problem by using a Time Division Multiplexing (TDM) system which uses distributed system of data acquisition and control in which pair of one twisted wire is used to transmit the multichannel data into different time slots. A low frequency carrier communication (LFCC) is used as a highly modular data point oriented building block which produces a cost effective solution.